inggris - Noerdin Basir; Hiraishi Tetsuya (Coastal and Ocean Journal (COJ), 2025)
While the XBeach model has been validated for complex coastal processes under storm conditions, its performance in predicting hydrodynamics and morphodynamic changes under controlled, small-scale regular wave scenarios—a critical gap for foundational calibration and understanding—remains less documented. This study addresses this gap by rigorously validating XBeach's capability to simulate regular wave propagation and the consequent coastal erosion in a controlled laboratory environment. The experiment was conducted in a 30 m flume at Kyoto University's UJIGAWA laboratory, using a piston-type wavemaker to generate nine regular wave cases (wave heights: 1.68–3.3 cm; periods: 0.83 s and 1.205 s). Model accuracy was quantitatively assessed using the Mean Absolute Error (MAE). The results demonstrate that XBeach proficiently simulates both hydrodynamic and morphodynamic processes. The validation for significant wave height yielded an MAE of 0.07, while the validation for the eroded area yielded an MAE of 0.05 (5%). Both MAE values are below the 10% sufficiency threshold, confirming the model's reliability in predicting wave transformation and erosion magnitude under regular wave forcing. This study provides a foundational validation benchmark, enhancing confidence in applying XBeach for coastal erosion prediction in scenarios dominated by monochromatic wave conditions.